Age as the Impact on Mortality Rate in Trauma Patients - Onchuda Wongweerakit; Osaree Akaraborworn; Burapat Sangthong; Komet Thongkhao (Critical Care Research and Practice)
Background. Globally, the fastest-growing population is that of older adults. Geriatric trauma patients pose a unique challenge to trauma teams because the aging process reduces their physiologic reserve. To date, no agreed-upon definition exists for the geriatric trauma patients, and the appropriate age cut point to consider patients at increased risk of mortality is unclear. Objectives. To determine the age cut point at which age impacts the mortality rate in trauma patients in Thailand. Materials and Methods. This was a retrospective cohort and prognostic analysis study conducted in trauma patients ≥40 years. Patient data were retrieved from the trauma registry database and hospital information system in Songklanagarind Hospital. The estimated sample size of 1,509 patients was calculated based on the trauma registry data. The age with the maximum mortality rate was used as the cut point to define the elderly population. Hospital cost, intensive care unit (ICU) length of stay, gender, precomorbidity, mechanism of injury, injury severity score (ISS), and trauma and injury severity score were analyzed for any correlation with mortality, and whether or not they were associated with elderly trauma patients. Results. A total of 1,523 trauma patients ≥40 years were included in the study. The median age in both the survival and death groups was 61 years, with gender in both groups being similar (p value = 0.259). In the multivariate logistic regression analyses, the adjusted odds ratio (OR) showed that increasing age was significantly associated with mortality (OR = 1.05; 95% CI, 1.02–1.07; p value <0.001). In the age group of 70 to 79 years and >80 years, the odds of mortality were significantly increased (OR 3.29, 95% CI, 1.24–8.68; p value = 0.016 and OR 3.29, 95% CI, 1.27–12.24; p value = 0.018, respectively). Conclusion. Age is a significant risk factor for mortality in trauma patients. The mortality significantly increased at the age of 70 and higher.